Photostability of Terbinafine Under UVA Irradiation: The Effect of UV Absorbers - Kryczyk‐Poprawa, Agata; Żmudzki, Paweł; Koczurkiewicz, Paulina; Pękala, Elżbieta; Hubicka, Urszula (Photochemistry and photobiology, 2019)
The photostability of drugs administered topically on unprotected skin is a complex phenomenon that could be connected with the loss of activity or, rather rarely, the occurrence of toxic degradation products. In this study, an in‐depth investigation of the photostability of terbinafine, in both solutions and formulations, was conducted, taking into account the presence of UV absorbers such as TiO2, ZnO, avobenzone, 3‐(4‐methylbenzylidene)camphor, octocrylene, benzophenone‐1 and benzophenone‐2. The clear photocatalytic degradation of terbinafine in ethanol solution was observed in the presence of TiO2 and/or ZnO. In other cases, terbinafine was stable, with the exception of, in the presence of octocrylene. The presumed degradation products of terbinafine were identified for the first time using LC/MS/MS, and transformation pathways were proposed. In the case of a cream formulation, the percentage of initial terbinafine content was almost unchanged in the presence of the UV absorbers benzophenone‐1, benzophenone‐2 and 3‐(4‐methylbenzylidene)camphor. In vitro cytotoxicity risk assessment of terbinafine based on photostability under UVA irradiation was evaluated using the human skin fibroblast BJ (ATCC® CRL‐2522™), and this showed no statistically significant difference in cell viability for all samples analyzed. In‐depth investigation of the photostability of terbinafine was conducted, taking into account the presence of UV absorbers such as TiO2, ZnO, avobenzone, 3‐(4‐methylbenzylidene)camphor, octocrylene, benzophenone‐1 and benzophenone‐2. The photocatalytic degradation of terbinafine was observed in the presence of TiO2 and/or ZnO. Using LC‐MS/MS, eleven presumable degradation products of terbinafine were identified. In the case of cream formulation, the percentage of initial terbinafine content was almost unchanged in the presence of benzophenone‐1, benzophenone‐2 and 3‐(4‐methylbenzylidene)camphor. In vitro cytotoxicity risk assessment of terbinafine after UVA irradiation was evaluated using the human skin fibroblast BJ (ATCC® CRL‐2522™).